Residential construction electrical wiring - Shopware (Firm) (New Jersey : Shopware Productions, 2008)
Hardwiring doesn't have to be hard. This video looks at some of the most frequently encountered appliances that get wired right into a house's electrical system: electric wall heaters, electric stoves, garbage disposals, dishwashers, thermostats, garage door openers, water heaters, and electric dryers
Title from title screen
DVD format
Keywords: Electric apparatus and appliances; Electric wiring, Interior